Parenterally administered vancomycin in 29 dogs and 7 cats (2003‐2017). (30th November 2018) - DeStefano, Ian M.; Wayne, Annie S.; Rozanski, Elizabeth A.; Babyak, Jonathan M.
Abstract : Background: Vancomycin is commonly used to treat resistant bacterial infections in people. Reported adverse effects of vancomycin in people include acute kidney injury (AKI), neutropenia, and systemic allergic reaction. Given the increased incidence of vancomycin‐resistant bacterial infections in people, support is growing for restriction of vancomycin. Objectives: To evaluate the use of intravenous (IV) vancomycin in a university teaching hospital and to describe potential adverse effects. Animals: Twenty‐nine dogs and 7 cats. Methods: Medical records of dogs and cats treated with IV vancomycin at the Foster Hospital for Small Animals between January 2003 and October 2017 were reviewed. Information recorded included signalment, infection source, vancomycin dosing, potential adverse effects, and outcome. Results: Vancomycin was used to treat infections from a range of sources with a variety of dosing intervals. The most common bacterial isolates susceptible to vancomycin included Enterococcus sp. (11/36, 30.6%), methicillin‐resistant Staphylococcus aureus (8/36, 22.2%), and methicillin‐resistant Staphylococcus pseudintermedius (2/36, 5.6%). AKI occurred in 6 of 36 patients (16.7%) during vancomycin treatment but could not definitively be attributed to vancomycin treatment in any patients because of illness severity, additional nephrotoxic treatments, or both. Neutropenia or allergic reaction was not documented in any animal. In 2 of 36 patients (5.6%), susceptibility data documented an infection that was only susceptible to vancomycin. Most patients survived to discharge (25/36, 69.4%). Conclusions and Clinical Importance: Adverse effects attributable to vancomycin were infrequent in dogs and cats. In most cases, there were potential alternative effective antimicrobials or lack of susceptibility data to support vancomycin treatment.